Examining the Effects of Financial and Nonfinancial Indices on Function of Social Security Organization - Hosseinzadeh, Amir; Davari, Behzad (International Review of Management and Marketing, 2017)
This article examines technique of “symmetrical evaluation” that is one of the newest techniques in of management accounting. There are firstly explained its main aspects. Then, there will be briefly explained equal evaluation process and necessary steps for its implementation. Then there will be provided some of its applications in various industries and different countries and its advantages are explained, in order to introduce scientific samples. Finally, there are presented conclusion and suggestions. It is concluded that technique of equal evaluation is one of the most important and newest techniques to evaluate operations of organization’s performance and it can be applied as a framework in military and strategic management in line with organizational changes; it is also supplementary of current techniques of management accounting in this field. However, its application should be based on cost and benefit as well as the presented steps in this article. Keywords: Performance evaluation, Symmetrical evaluation, Strategic management accounting JEL Classifications: L1, L25